2020
DOI: 10.13057/biodiv/d210713
|View full text |Cite
|
Sign up to set email alerts
|

Investigating new SNPs of CAST, CAPN and SCD genes in 5’UTR of Bali cattle

Abstract: Abstract. Jakaria, Ulum MF, Lestari D, Akwila S, Sihite DEWT, Priyanto R, Muladno, Sumantri C. 2020. Investigating new SNPs of CAST, CAPN and SCD genes in 5’UTR of Bali cattle. Biodiversitas 21: 2971-2976. The present investigation aims to explore specific SNPs of Bali cattle, focusing mainly on CAST, CAPN, and SCD genes in 5'UTR. DNA of Bali cattle (25 individuals) from Breeding Centre of Bali cattle in Bali Province, Indonesia, were extracted according to the protocol of GenAID. Amplification of the CAST, CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…A previous study has been reported that the 5'UTR region of CAPN1 gene was polymorphic in Bali cattle nevertheless quite low nucleotide diversities (Pi) of 0.00632 (Jakaria et al 2020). Previously, the role of CAPN gene has been reported that the u-calpain is the enzyme proteolysis, contributes to meat tenderness (Avilés et al 2013;Lozano et al 2016).…”
Section: Polymorphisms Of Snp G232 G>t 5'utr Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has been reported that the 5'UTR region of CAPN1 gene was polymorphic in Bali cattle nevertheless quite low nucleotide diversities (Pi) of 0.00632 (Jakaria et al 2020). Previously, the role of CAPN gene has been reported that the u-calpain is the enzyme proteolysis, contributes to meat tenderness (Avilés et al 2013;Lozano et al 2016).…”
Section: Polymorphisms Of Snp G232 G>t 5'utr Regionmentioning
confidence: 99%
“…The primer sequences of the CAPN1 gene based on Jakaria et al (2020) were previously designed at the 5'UTR region using GenBank database sequence (NCBI) with access code AH009246.3. The primer sequences included forward and reverse as follows F: 5'-CCCTTCCCACCCAGATAGG-3', R: 5'-CCTGGAGACCGTGAGGAAC-3' and the PCR product was 478 bp.…”
Section: Primer Design and Dna Amplificationmentioning
confidence: 99%